Four new species of the fern genus Goniopteris C. Presl (Thelypteridaceae) from Brazilian Atlantic Forest - Salino, Alexandre; Leroy, Carolina Jesus; Moura, Luiza Costa; Moura, Ingridy Oliveira (Phytotaxa, 2016)
Four new species of Goniopteris from Brazil are described and illustrated: Goniopteris smithii and G. windischii are narrowly endemic to southern Bahia, G. seidleri is restricted to the mountains of Espírito Santo and Rio de Janeiro states, and G. subdimorpha is endemic to semideciduous forests of Minas Gerais state.